Mixed integer programming (mip) model for production scheduling in an automotive part company - Kamaruddin, Aisyah Nabilah (2010)
Scheduling is defined as the allocation of resources to task over time in such a way that a predefined performance measure is optimized. Scheduling is a decision making function that plays an important role in manufacturing industries. In this research, a model of Mixed Integer Programming is proposed based on the scheduling problems in an automotive part production company. This mathematical method provides a theoretical framework for the formulation and solution of the models which involve the translation of the real problem into a model. This model targets to optimize the scheduling production in order to increase productivity. All standard constraints encountered in the production scheduling are included in the model (machine capacity, material balances, manpower restrictions and inventory limitations). Machine setup time changeover and cost changeover for the different product will influence the arrangement of scheduling process. The objective function that is minimized considers all major sources of variable cost that depend on the production schedule, such as changeover cost between products, inventory cost and labor cost. The result from this study are presented and discussed based on the optimal production schedule.